Original paperTransradial approach for vertebral artery stenting - Maciejewski, Damian; Tekieli, Łukasz; Kabłak-Ziembicka, Anna; Paluszek, Piotr; Trystuła, Mariusz; Wójcik-Pędziwiatr, Magdalena; Machnik, Roman; Pieniążek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introductuion: Symptomatic severe vertebral artery (VA) stenosis may be treated safely with stent supported angioplasty via femoral access. There is limited clinical data on transradial approach for VA angioplasty in case of peripheral artery disease. Aim : To evaluate the safety and efficacy of transradial angioplasty of symptomatic VA stenosis. Material and methods: Fifteen patients (age 66 ±7.4 years, 73% men, with VA > 80% stenosis, 11 right-side, all symptomatic from posterior circulation (history of stroke, TIA, or chronic ischaemia symptoms)) with peripheral artery disease (PAD) or unsuccessful attempt via femoral approach were scheduled for VA angioplasty by radial access. Clinical and duplex ultrasound (DUS) follow-up were performed before discharge and 1, 12, and 24 months after VA angioplasty. Result s: The technical success rate was 100%. In all cases VA angioplasty was performed with the use of single balloon-mounted stent (9 bare metal stents, 6 drug-eluting stents). The mean NASCET VA stenosis was reduced from 85.3% to 5.3% (p < 0.001). No periprocedural death, stroke, myocardial infarction, or transient ischaemic attack occurred. During 24-months follow-up, in 12 of 15 patients chronic ischaemia symptoms release was observed, and no new acute ischaemic neurological symptoms were diagnosed in all patients. One patient died 20 months after intervention from unknown causes. There was one symptomatic borderline VA in-stent stenosis 12 months after angioplasty. Conclusions : Transradial VA stenting may be a very effective and safe procedure, and it may constitute an alternative to the femoral approach in patients with symptomatic VA stenosis.